Paricalcitol inhibits the Wnt/beta-catenin signaling pathway and ameliorates experimentally induced arthritis - Yolbas, Servet; Yildirim, Ahmet; Tektemur, Ahmet; Celik, Zulfinaz Betul; Onalan Etem, Ebru; Ozercan, Ibrahim Hanifi; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: The Wnt/beta-catenin pathway has important biological activities, including the differentiation of cells and joint formations. The aim of our study was to determine the effect of paricalcitol on experimentally induced arthritis. Materials and methods: Type II collagen combined with Freund's adjuvant was applied to induce arthritis in Wistar albino female rats. Paricalcitol (0.3 mu g/kg daily) was subcutaneously injected starting 1 day after collagen applications (prophylactic group) or 1 day after the onset of arthritis (therapeutic group), until day 29. Results: The 29th day arthritis scores were lower compared to the 13th day scores in the paricalcitol groups (P < 0.05), while they were higher in the arthritis group (P < 0.05). Marked cartilage-bone destruction and extensive perisynovial inflammation were detected in the arthritis group. Decreased cartilage-bone destruction and perisynovial inflammation in the paws were observed in the paricalcitol groups. The tissue mRNA levels of DKK1, Wnt5a, and axin-2 were higher in the arthritis group than in the control group. In the paricalcitol groups, mRNA expressions were lower than in the arthritis group. Conclusion: The present study shows that the Wnt/beta-catenin signaling pathway is active in arthritis. Moreover, paricalcitol ameliorates arthritis via inhibiting the Wnt/beta B-catenin pathway. Paricalcitol and the Wnt/beta-catenin pathway are candidates for research in human rheumatoid arthritis.
Keywords: Rheumatoid arthritis; Wnt/beta-catenin signaling pathway; paricalcitol